Perancangan dan Implementasi Aplikasi Manajemen Iklan pada Mesin Penjual Otomatis Smartfren - Fawwaz Baahir Hidayatullah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
This research designs and builds an advertising management application program on a Smartfren vending machine. This design needs to be done to make it easier for admins so they don't have to manage ads manually on vending machines. Smartfren vending machines are electronic machines that can be used by Smartfren customers to carry out transactions such as buying data packages, buying credit, paying bills, and other Smartfren services. This machine contains advertisements in the form of images and videos displayed as promotions for Smartfren products. The purpose of designing this system is that the ads displayed on the vending machine are dynamic. In this design, a WebSocket connection is used as a communication protocol between the server and the client. By using research and development methods where data from interviews and observations will be developed through a process of design, implementation and testing. The main result of system design is that admins can add, change and delete advertisements displayed on vending machines.